2019
DOI: 10.1038/s41598-019-56073-y
|View full text |Cite|
|
Sign up to set email alerts
|

In vitro metabolomic footprint of the Echinococcus multilocularis metacestode

Abstract: Alveolar echinococcosis (AE) is a zoonotic disease that is deadly if left untreated. AE is caused by the larval metacestode stage of the cestode Echinococcus multilocularis. Better knowledge on the host-parasite interface could yield novel targets for improvement of the treatment against AE. We analyzed culture media incubated with in vitro grown E. multilocularis metacestodes by 1H nuclear magnetic resonance spectroscopy to identify the unknown metabolic footprint of the parasite. Moreover, we quantitatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 75 publications
1
18
1
Order By: Relevance
“…An essential prerequisite for the identification of novel targets is a profound knowledge of the parasite biochemistry and its metabolic requirements. A recent publication by Ritler et al (2019) reported on the molecular footprint of E. multilocularis metacestodes, and by analysing the metabolic host-parasite interface in vitro , a number of potentially targetable metabolic pathways were identified. An important finding was that not only the ubiquitous energy source glucose, but also the amino acid threonine, was consumed by the parasite at high levels.…”
Section: Identification Of Novel Drugs Against Alveolar Echinococcosimentioning
confidence: 99%
“…An essential prerequisite for the identification of novel targets is a profound knowledge of the parasite biochemistry and its metabolic requirements. A recent publication by Ritler et al (2019) reported on the molecular footprint of E. multilocularis metacestodes, and by analysing the metabolic host-parasite interface in vitro , a number of potentially targetable metabolic pathways were identified. An important finding was that not only the ubiquitous energy source glucose, but also the amino acid threonine, was consumed by the parasite at high levels.…”
Section: Identification Of Novel Drugs Against Alveolar Echinococcosimentioning
confidence: 99%
“…Interestingly, the S. solidus glutamate dehydrogenase isozyme A0A0X3P860 contains the GFGNVG sequence and Glu (278), which are more typical for isoforms that provide the deamination reaction rather than the addition of ammonia (Oliveira et al, 2012;Prakash et al, 2018;Grzechowiak et al, 2020). Therefore, in adult flatworms, this enzyme appears to provide NADPH for redox reactions, probably for the malate dismutation pathway in mitochondria (Smyth and McManus, 2007;Ritler et al, 2019).…”
Section: Discussion Proteomic Changes In S Solidis Are Mostly Energy-relatedmentioning
confidence: 99%
“…In cestodes, glucose oxidation leads either to the formation of lactate, or to the formation of oxaloacetate, and then malate, which is converted into succinate and acetate in mitochondria (CO 2 fixation pathway; malate dismutation pathway) (Smyth and McManus, 2007;Ritler et al, 2019). This cleavage occurs at the level of phosphoenolpyruvate, for which pyruvate kinase (PK) and phosphoenolpyruvate carboxykinase (PEPCK) compete (Das et al, 2015) (Fig.…”
Section: Discussion Proteomic Changes In S Solidis Are Mostly Energy-relatedmentioning
confidence: 99%
“…Metabolic profiling approaches have been widely used in various studies on diseases caused by flatworms such as Fasciola hepatica and roundworms such as Onchocerca volvulus [ 32 35 ]. Nevertheless, reports on the application of the LC–MS/MS-based metabolomics approach in echinococcosis are limited [ 36 ]. In this study, we used a LC–MS/MS system-based metabolomics approach and multivariate statistical analyses to investigate the molecular mechanism of CE and to provide a potential valuable reference for the diagnosis of CE.…”
Section: Introductionmentioning
confidence: 99%